The structure of linear extensions with the Favard type conditions II. Linear extensions with the additivity property of recurrent motions - Glavan, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
We study the structure of linear extensions with external powers satisfying the condition of additivity of recurrent motions.